1993
DOI: 10.1002/art.1780360809
|View full text |Cite
|
Sign up to set email alerts
|

Presence of estrogen‐binding sites on macrophage‐like synoviocytes and cd8+, cd29+, cd45ro+ t lymphocytes in normal and rheumatoid synovium

Abstract: Objective. To study the presence of estrogenbinding sites (EBS) in the synovial tissues of male and female patients with rheumatoid arthritis (RA) and in age-and sex-matched healthy controls.Methods. Both type 1 (high affinity, low binding capacity) and type 2 (reduced affinity, higher binding capacity) EBS were investigated in both soluble and nuclear fractions of homogenized synovial tissue sam- ples by a dextran-coated charcoal method. To determine what type of synovial cell was positive for EBS, cryosectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 61 publications
0
32
0
1
Order By: Relevance
“…The monocyte/phagocyte system has been reported to be exquisitely sensitive to estrogens, supporting the view that gonadal steroids are primary regulators of various sides of the immune response [Grossman, 1989]. The presence of ER in different immune cell types has been repeatedly reported by others and our own group [Cohen et al, 1983;Danel et al, 1983;Carbone et al, 1986;Cutolo et al, 1993Cutolo et al, , 1996. In addition, estradiol has been involved in the regulation of macrophage activity, especially in the bone [Oursler et al, 1991].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The monocyte/phagocyte system has been reported to be exquisitely sensitive to estrogens, supporting the view that gonadal steroids are primary regulators of various sides of the immune response [Grossman, 1989]. The presence of ER in different immune cell types has been repeatedly reported by others and our own group [Cohen et al, 1983;Danel et al, 1983;Carbone et al, 1986;Cutolo et al, 1993Cutolo et al, , 1996. In addition, estradiol has been involved in the regulation of macrophage activity, especially in the bone [Oursler et al, 1991].…”
Section: Discussionmentioning
confidence: 70%
“…ER content and status of THP-1 cells was determined by means of LBA, using a modi®ca-tion of a previously described method [Castagnetta et al, 1983[Castagnetta et al, , 1987bCutolo et al, 1993Cutolo et al, , 1996. The cell pellets were washed twice in icecold PBS-A, resuspended in 4 ml of HED buffer (Hepes 10 mM, EDTA 1.5 mM, Dithiothreitol 0.5 mM, pH 7.4) and gently te¯on-glass homogenized for 2 Â 10 s bursts at a setting of 600±800 rpm on a Potter S cooling system homogenizer (B.Braun Biotech Int.…”
Section: Lbamentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are the major immune cell present within the synovial tissues and are recruited in high numbers in RA, suggesting that a majority of IL-1 and TNF␣ release within the joint is from this cell type (17). Subsequent to and building upon these studies, the nuclear receptor estrogen receptor ␤ (ER␤) was detected in macrophages, revealing a mechanism by which estrogen can act to effect molecular signals within the cells (18,19). Investigators in our laboratory have detected the presence of ER␣ and ER␤ transcripts and ER␤ protein in primary macrophages and have found that removal of estrogen did not have a dramatic effect on the amount of ER protein present, suggesting that estrogen does not regulate its own receptor in monocyte-derived macrophages (20).…”
Section: Conclusion Estrogen Can Modulate Proinflammatory Cytokine Rmentioning
confidence: 96%
“…-11 However, it is only recently that androgen and oestrogen receptors have been detected in synovial macrophages (mCs) of normal and rheumatoid synovial tissues, by immunostaining of cryosections and by biochemical characterization in homogenized tissues. 12,13 The presence of androgen receptors on mCs induced us to analyse the metabolic pathway for androgens.…”
Section: Introductionmentioning
confidence: 99%